The Buck-boost converter in photovoltaics for battery chargers - imam saukani; Eko Nuraini; Agus Sukoco Heru Sumarno; Rina Tri Turani Saptawati; Imanur Islahunufus; Fi Imanur Sifaunnufus Ms (Journal of Evrímata: Engineering and Physics, 2024)
Alternative energy is energy that is widely developed by scientists nowadays, especially in terms of electricity. Currently, the alternative energies that are widely developed are wind power, hydropower, geothermal energy, and solar power. Solar power is a promising energy source in Indonesia. The utilization of solar energy requires photovoltaics to convert solar energy into electricity, while for charging a12V/7Ah battery, a buck-boost converter is used. However, the use of the buck-boost converter still has some shortcomings, such as reversed voltage polarity. To address this issue, it is proposed to use a2-switch buck-boost converter. With the2-switch buck-boost converter, it is capable of charging the battery with an initial voltage of19V, which is then reduced to14.25V to charge the battery with an initial voltage of10.08V to11.16V within60 minutes, maintaining the same polarity as the initial input and with a maximum current from the photovoltaic of3.48A. In this thesis, Atmega16 is used to control the2-switch buck-boost converter and a50Wp photovoltaic with a maximum voltage of 21V and a current of 3.48A..